Productive Zakat Scholarship of National Amil Zakat Agency of Bandar Lampung City in Improving Human Resources - Maraliza, Helmahelma; Mu’in, Fathul; Febriati, Nurullia (Nizham Jurnal Studi Keislaman, 2024)
Zakat has a strategic role in reducing poverty and increasing the economic empowerment of the people.However, in reality, most of the zakat is only managed traditionally so that the benefits have not been felt.The purpose of this research is to reveal productive zakat in the form of scholarships from the National Amil Zakat Agency or Baznas Bandar Lampung City in improving human resources from a legal perspective. This research is included in field research whose data is obtained from Baznas Bandar Lampung City.This research concludes that Baznas Bandar Lampung City provides scholarships to as many as 25 students from UIN Negeri Raden Intan Lampung and ITERA.Zakat funds distributed by Baznas Bandar Lampung City amounted to Rp. 66,900,000.In the perspective of Islamic law, scholarship zakat is valid and included in productive zakat.This is based on the arguments of the Koran, Prophetic traditions and MUI Fatwa in 1996. Zakat scholarships provide many benefits, including increased access to education, which helps mustahik to access higher education. Zakat scholarship is also able to improve the quality of human resources because it succeeds in producing scholars who have knowledge so that they are ready to compete in the world of work and are involved in regional development.